Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 72 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Drepane Cuvier, 1831", "Country is India" ] } The dataset includes 72 records from 10 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001597-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences